Correction to: Proposal for a definition for response to treatment, inactive disease and damage for JIA associated uveitis based on the validation of a uveitis related JIA outcome measures from the Multinational Interdisciplinary Working Group for Uveitis in Childhood (MIWGUC) - Ivan Foeldvari; Jens Klotsche; Gabriele Simonini; Clive Edelsten; Sheila T. Angeles-Han; Regitze Bangsgaard; Joke de Boer; Gabriele Brumm; Rosa Bou Torrent; Tamas Constantin; Cinzia DeLibero; Jesus Diaz; et al. (BMC, 2020)
Following publication of the original article [1], we have been notified that the author Joan Calzada should not have been included to the team of authors. The authors' team, thus, should be as follows: